2010
DOI: 10.1057/rlp.2010.2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of defects in Malaysian university buildings: Providers’ perspective

Abstract: Facilities management is taking centre stage in the discourse of academic institutions because of its relevance to facilitating learning, teaching and conducting research. University buildings are an important part of these facilities and considerable resources are committed to their design, construction and maintenance. This article is based on the premise that if there is information on the criteria that infl uence the maintenance of university buildings, the characteristics of defects in university building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…This is then the optimal interval should be adhered to all possible circumstances. If there is uncertainty about the value of the particular parameter required in the analysis [9]- [12], then the evaluation of the total cost curve for various values of uncertain parameter, could affect the optimal solution. In order to further assist engineers in deciding what appropriate replacement policy should be, it is useful to plot the total cost per unit time curve.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…This is then the optimal interval should be adhered to all possible circumstances. If there is uncertainty about the value of the particular parameter required in the analysis [9]- [12], then the evaluation of the total cost curve for various values of uncertain parameter, could affect the optimal solution. In order to further assist engineers in deciding what appropriate replacement policy should be, it is useful to plot the total cost per unit time curve.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Hence, further issues such as space inefficiency, ventilation discomfort and inefficient of energy use may decrease the performance of the buildings from time to time [1]- [4]. Performance failure not only affects the building sustainability, but the users are also affected by the failure of building performance [5]. To optimise the performance of HEB, it should avoid allocating the occupants, visitors and passers-by at risk [6].…”
Section: Introductionmentioning
confidence: 99%
“…From the cases that have been reported, it can be concluded that decay and failures are fatal and critical because they are harmful to the users and the building itself, causing damage, serious injuries and death [7,8,9]. Buildings are designed as structural systems, and consequently, when a major component of the building fails, it can trigger a series of failures [10,11,12]. This paper will identify and differentiate the common decay and deterioration faced by educational buildings.…”
Section: Introductionmentioning
confidence: 99%